2019
DOI: 10.1002/hyp.13445
|View full text |Cite
|
Sign up to set email alerts
|

A classification approach to reconstruct local daily drying dynamics at headwater streams

Abstract: Headwater streams (HSs) are generally naturally prone to flow intermittence. These intermittent rivers and ephemeral streams have recently seen a marked increase in interest, especially to assess the impact of drying on aquatic ecosystems. The two objectives of this work are (a) to identify the main drivers of flow intermittence dynamics in HS and (b) to reconstruct local daily drying dynamics. Discrete flow states—“flowing” versus “drying”—are modelled as functions of covariates that include information on cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
(77 reference statements)
0
17
0
Order By: Relevance
“…Arrows depict the links between each compartment and variables within stations is not only costly but may be prohibitive due to active geomorphological processes and restricted accessibility (Beaufort, Carreau, & Sauquet, 2019;Beaufort, Lamouroux, Pella, Datry, & Sauquet, 2018). Our conceptual model shows that climate is the main driver affecting all processes through precipitation, wind action, and temperature fluctuations, which are mediated by catch- Conceptual framework compartmentalizing the natural and human-induced exogenous and indigenous variables that drive Mediterranean intermittent rivers and ephemeral streams.…”
Section: The Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Arrows depict the links between each compartment and variables within stations is not only costly but may be prohibitive due to active geomorphological processes and restricted accessibility (Beaufort, Carreau, & Sauquet, 2019;Beaufort, Lamouroux, Pella, Datry, & Sauquet, 2018). Our conceptual model shows that climate is the main driver affecting all processes through precipitation, wind action, and temperature fluctuations, which are mediated by catch- Conceptual framework compartmentalizing the natural and human-induced exogenous and indigenous variables that drive Mediterranean intermittent rivers and ephemeral streams.…”
Section: The Challengesmentioning
confidence: 99%
“…The complexity of Mediterranean IRES arises not only from the number and variability of the controlling variables but also from the interactions between them. Our conceptual model shows that climate is the main driver affecting all processes through precipitation, wind action, and temperature fluctuations, which are mediated by catch- stations is not only costly but may be prohibitive due to active geomorphological processes and restricted accessibility (Beaufort, Carreau, & Sauquet, 2019;Beaufort, Lamouroux, Pella, Datry, & Sauquet, 2018). On the ground wet and dry mapping is sometimes used to compensate the absence of gauges (Datry, Fritz, & Leigh, 2016;Turner & Richter, 2011).…”
Section: The Challengesmentioning
confidence: 99%
“…Background elevation data from https://land.copernicus.eu/imagery-in-situ/eu-dem/eu-dem-v1-0-andderived-products. The stream network was obtained from http://www.sandre.eaufrance.fr/ Hydrological models (Gutiérrez-Jurado, Partington, Batelaan, Cook, & Shanafield, 2019;Ward, Schmadel, & Wondzell, 2018;Williamson, Agouridis, Barton, Villines, & Lant, 2015;Yu, Bond, Bunn, Xu, & Kennard, 2018), topographic data (Prancevic & Kirchner, 2019) and statistical approaches (Beaufort, Carreau, & Sauquet, 2019;Durighetto, Vingiani, Bertassello, Camporese, & Botter, 2020;González-Ferreras & Barquín, 2017;Jaeger, Sando, et al, 2019;Konrad & Rumsey, 2019;Russell, Gale, Muñoz, Dorney, & Rubino, 2015;Snelder et al, 2013) have been used to predict where streams are temporary and can be used to determine where additional data on the state of temporary streams may be most useful. However, to train and validate these models, more observations of the state of temporary streams and stream network dynamics are needed.…”
Section: F I G U R Ementioning
confidence: 99%
“…Previous research demonstrated the potential of parametric approaches for wet/dry mapping [15], flow permanence simulation [16] and estimating probability of intermittence [17]. Furthermore, neural networks and random forest approaches have been demonstrated to be well suited for statistical simulation of intermittence [18]. Other recent studies have also taken a random forest approach to simulating intermittence [19][20][21], and some have compared approaches including neural networks, regression trees and multivariate adaptive regression splines [18,22].…”
Section: Introductionmentioning
confidence: 99%